2018
DOI: 10.3390/agronomy8120292
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Potassium Application for Hybrid Rice (Oryza sativa L.) in Coastal Saline Soils of West Bengal, India

Abstract: The present study assesses the response of hybrid rice (variety Arize 6444) to potassium (K) application during rainy (wet) seasons of 2016 and 2017 in coastal saline soils of West Bengal, India. The study was conducted at the Regional Research Farm, Bidhan Chandra Krishi Viswavidyalaya, Kakdwip, West Bengal. The soil is clayeywith acidic pH (5.91), saline (Electrical conductivity/EC 1.53 dS m−1) and of high K fertility (366 kg ha−1). The experimental plots were laid out in a randomized complete block design w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 18 publications
(23 reference statements)
3
7
0
Order By: Relevance
“…Meena et al (2003) [22] also reported that increased level of potassium showed significant influence on dry matter accumulation. The result of this experiment tuned with the findings of Abdel et al (2004) [1] , Bahmaniar et al (2007) [5] and Banerjee et al (2018) [6] . The exogenous application of K has direct effects on the growth and total biomass allocation in rice (Samejima et al, 2005) [27] .…”
Section: Resultssupporting
confidence: 91%
“…Meena et al (2003) [22] also reported that increased level of potassium showed significant influence on dry matter accumulation. The result of this experiment tuned with the findings of Abdel et al (2004) [1] , Bahmaniar et al (2007) [5] and Banerjee et al (2018) [6] . The exogenous application of K has direct effects on the growth and total biomass allocation in rice (Samejima et al, 2005) [27] .…”
Section: Resultssupporting
confidence: 91%
“…Split application of potassium registered significantly superior effect over basal application with respect to dry matter accumulation (g m -2 ) in context of all the levels of applied potassium and the maximum dry matter was accumulated under S 3 while its lowest value was received in case of basally applied K (S 1 ).The split application of potassium controlled the opening and closing of stomata and promoted better photosynthetic activities resulting into higher dry matter production. Similar result of increased dry matter production with increased level of potassium was also reported by Meena et al (2003) [17] , Abdel et al (2004) [1] , Bahmaniar et al (2007) [4] and Banerjee et al (2018) [6] . Effect on yield attributing characters: Important yield parameters of rice are panicle m -2 , number of spikelet and fertile spikelet, 1000 grain weight which were recorded in present.…”
Section: Effect On Dry Matter Accumulationsupporting
confidence: 83%
“…The function of potassium in increasing assimilating power and better translocation efficiency resulted in the expression of better yield attributes in the form of effective tillers m -2 , panicle length, grains per panicle (Arivazhagan and Ravichandran, 2005) [2] . Banerjee et al (2018) [6] also reported that increase in total photosynthetic rate and net assimilation rate at heading and maturing stages with high K application might have led to greater dry matter production and effective tillers., Higher yield by split application of potassium might be due to enhanced grain weight which was the result of delay in abscisic acid (ABA) peak by four to five days causing delayed maturation and increased carbohydrate translocation to the seeds (Yuan et al, 1993) [26] .…”
Section: Effect On Dry Matter Accumulationmentioning
confidence: 99%
“…The AEP and AEK were significantly higher in STCR-based nutrient management practices than the application of the GRD alone, except for the AEK in STCR TY2FYM and STCR TY1FYM, where they were at par with the GRD. An AEN of 6.8-34.2 [63] and AEK of 28.4-55.3 [64] in rice crops have been reported. Similarly, the REN, REP, and REK increased significantly with STCR treatments compared to application of the GRD alone, except for REK, where the STCR TY1FYM and GRD were comparable.…”
Section: Nutrient Use Efficiency (Nue)mentioning
confidence: 98%
“…Except for STCR TY2 and STCR TY1, all other STCR-based nutrient management practices were comparable with the GRD in case of PPFK. A PFPK of 62.42-191.33 has been reported [64]. In general, the reciprocal internal use efficiency (RIUE) followed the order RIUEN>RIUEK>RIUEP [25].…”
Section: Nutrient Use Efficiency (Nue)mentioning
confidence: 99%